Network pharmacology reveals Ficus. Carica. L latex as a potential therapeutic agent for gastric ulcers by modulating inflammation and promoting repair - Nourhan Hisham Shady; Mohamed Hisham; Hend Samy Abdullah; Sherif A. Maher; Amgad Albohy; Mahmoud A. Elrehany; Ahmed M. Sayed; Esam S. Allehyani; Manal M. Khowdiary; Ahmed M. Shawky; Usama Ramadan Abdelmohsen (PLoS ONE, 2025)
The primary objective of our research is to investigate the gastroprotective impact of Ficus. carica L. latex extract (FCL). Metabolic profiling based on HR- LCMS for the extract led to the annotation of 20 compounds. Additionally, the gastro-protective activity of the latex extract was evaluated in vivo using male albino rats. FCL significantly alleviated the indomethacin-induced ulceration and reduced the ulcer index. Furthermore, the inflammation caused by indomethacin was seen to diminish due to the downregulation of the production of certain genes ( IL-6, and TNF-α, IL-1β ). Besides, FCL considerably reduced the elevated TGF-β, and IGF-1, COX-2 relative gene expression. Likewise, FCL dramatically raised EGF and KGF relative gene expression, demonstrating its beneficial impact in ulcer healing. The antioxidant ability of FCL was assessed by in vitro experiments utilizing hydrogen peroxide and superoxide radical scavenging, which demonstrated significant antioxidant capacity. Employing network pharmacology, we identified 10 hub genes central to peptic ulcer disease and conducted molecular docking studies screening interactions between FCL extract compounds and these hubs along with anti-inflammatory targets including FGFR, TGF-βR, IGFR-1R and IL-1R1 involved in ulcer healing. Additionally, an in-silico study using annotated FCL compounds highlighted Ficuseptin-C, Ficuseptin-B and Ficusin-A in the extract may contribute to its antiulcer properties. The present study highlighted the potential of FCL as a promising natural gastro-protective agent.